Reexamining Phillips Curve: An Empirical Analysis From Structural Vector Autoregression - Sasongko, Gatot; Patricia Yolanda, Martha; Dolfriandra Huruta, Andrian; Kim, Min-Sun (Industrija, 2022)
In the literature, the existence of the Phillips curve in every country has been extensively explored. The goal of this research is to investigate the inflation-unemployment trade-off in Indonesia. We used secondary data for 1977 through 2019 from the World Bank for analysis. The Structural Vector Autoregression (SVAR) results revealed a negative connection between unemployment and inflation. There is a one-way relationship between unemployment and inflation in particular. We discovered several factors that influence unemployment. Those factors include working population over 15 years old according to the primary employment (both field and status) and Gross Domestic Product at constant prices according to expenditures.